2016
DOI: 10.1186/s11671-016-1607-2
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Gold Nanoparticles and Plant Adaptation Potential

Abstract: Use of metal nanoparticles in biological system has recently been recognised although little is known about their possible effects on plant growth and development. Nanoparticles accumulation, translocation, growth response and stress modulation in plant system is not well understood. Plants exposed to gold and gold nanoparticles have been demonstrated to exhibit both positive and negative effects. Their growth and yield vary from species to species. Cytoxicity of engineered gold nanoparticles depends on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(84 citation statements)
references
References 74 publications
2
80
0
2
Order By: Relevance
“…Nanomaterials fabricated from plants, fungi and bacteria have several potential applications in all fields of science and technology [110]. The reduction of metal ions occur by the proteins, amines, amino acids, phenols, sugars, ketones, aldehydes and carboxylic acids present in the plants and microbes.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials fabricated from plants, fungi and bacteria have several potential applications in all fields of science and technology [110]. The reduction of metal ions occur by the proteins, amines, amino acids, phenols, sugars, ketones, aldehydes and carboxylic acids present in the plants and microbes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the shift of the peak from 1120 to 1200 cm −1 corresponding to the group of amino acids in the pure green tea spectrum, and also in the PtII NPs spectrum, confirmed that the biomolecules in green tea are responsible for the reduction of H 2 PtCl 6 . The binding of biomolecules to PtII NPs through the amino acid groups can be confirmed by the shift in the NH frequency from 2860 to 2790 cm −1 . Studies that investigated the reductive activity of flavonoids have demonstrated that the activity of these compounds depends on the presence of specific structural groups in their molecules .…”
Section: Resultsmentioning
confidence: 96%
“…Biosynthesis and fabrication of metal and metal oxide nanoparticles by the aid of intracellular and extracellular functional groups and enzymes from plants, bacteria, fungi, algae, and viruses have recently gained much interest (Siddiqi and Husen, 2016). Bacteria such as Rhodopseudomonas capsulate, Deinococcus radiodurans, Geobacillus sp., B. subtilis, and B. casei have been documented for the synthesis and capping of Au-NPs (He et al, 2008;Li et al, 2016;Correa-Llanten et al, 2013;Reddy et al, 2010;Kalishwaralal et al, 2010).…”
Section: Fabrication Of Nanoparticlesmentioning
confidence: 99%
“…Owing to their small size and high surface-tovolume ratio, the GLPÀAgNPs ruptured the cell wall and caused cell lysis in the test pathogen, V. cholera (Gahlawat et al, 2016) Metal and metal oxide nanoparticles have been also been extracellularly produced and fabricated using algal species such as Chlorella vulgaris, Chlamydomonas reinhardtii, Fucus vesiculosus, Ecklonia cava, Spirulina platensis, Oscillatoria willei, Sargassum muticum, Stoechospermum marginatum, etc. (Siddiqi and Husen., 2016). Iron oxide nanoparticles of 18 6 4 nm size were prepared using an aqueous extract of the brown alga, S. muticum at 25 C. The reduction in the FeCl 3 to Fe 3 O 4 nanoparticles was brought about by the polysaccharides present in the algal extract (Mahdavi et al, 2013).…”
Section: Fabrication Of Nanoparticlesmentioning
confidence: 99%